Reelection threshold contracts in politics - Gersbach, Hans; Liessem, Verena (CESifo working papers, 2001)
When politicians are provided with insufficient incentives by the democratic election mechanism, we show that social welfare can be improved by threshold contracts. A threshold incentive contract stipulates a performance level which a politican must reach in order to have the right to stand for reelection. Read my lips would turn into read my contracts. Reelection thresholds can be offered by politicians during campaigns and do not impair the liberal principle of free and anonymous elections in democracies.
Keywords: Arbeitspapier; Graue Literatur; Anreiz; Kontrakttheorie; Spieltheorie; Ökonomische Theorie der Demokratie; Demokratie; Wahl